Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1128/jmbe.v19i1.1539
|View full text |Cite
|
Sign up to set email alerts
|

Science in the Eye of the Beer-Holder—How To Put On an Effective Pint of Science: The Adelaide Experience

Abstract: “Pint of Science” is an outreach activity bringing the latest scientific discoveries to the community in the relaxed atmosphere of a pub. Founded in the United Kingdom in 2012, this three-night festival in May is now held annually in cities around the world. Today, Pint of Science contributes to science education and engages peers and the public alike, demystifying science at a pub near you. This article gives advice about how to organize a Pint of Science festival, as exemplified by the Adelaide/South Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Many of those we interviewed suggested that one way to increase the reach and range of topics and its diversity is to increase collaborations with local research institutions and universities. These findings are consistent with recommendations from the PoST team [2].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Many of those we interviewed suggested that one way to increase the reach and range of topics and its diversity is to increase collaborations with local research institutions and universities. These findings are consistent with recommendations from the PoST team [2].…”
Section: Discussionsupporting
confidence: 92%
“…In 2018, Pint of Science (PoS) was held in 21 countries but as far as we know, this is the first paper that reports the quantitative and qualitative evaluation results from both organizers and the audience members who participated. Previous PoS publications consisted mainly of reflections from the organizing committee [2, 19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations